2021
DOI: 10.1021/acsnano.0c10374
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Flexible Visible-Blind Ultraviolet Photodetectors with Two-Dimensional Electron Gas Based on Unconventional Release Strategy

Abstract: Interdigitated photodetectors (IPDs) based on the twodimensional electron gas (2DEG) at the AlGaN/GaN interface have gained prominence as high sensitivity ultraviolet (UV) PDs due to their excellent optoelectronic performance. However, most 2DEG-IPDs have been built on rigid substrates, thus limiting the use of 2DEG-IPDs in flexible and wearable applications. In this paper, we have demonstrated high performance flexible AlGaN/GaN 2DEG-IPDs using AlGaN/GaN 2DEG heterostructure membranes created from 8 in. AlGaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The lowest NEP and the highest D* are calculated to be 1.51 × 10 −15 W Hz −1/2 and 6.01 × 10 11 Jones, respectively, demonstrating the ability to detect a weak light signal (Figure S5, Supporting Information). It is worth noting that the present GaSe nanobelt displays much better photoelectric performance than previously reported GaSe nanosheet, including mechanically exfoliated GaSe nanosheets [ 20,39 ] and gas‐phase grown GaSe nanosheets, [ 40 ] which is comparable to or even better than that of traditional UWBG DUV photodetectors [ 12–15 ] (shown in Table 1 ), making it a promising candidate for application in future high‐performance DUV photodetector‐based devices and systems.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The lowest NEP and the highest D* are calculated to be 1.51 × 10 −15 W Hz −1/2 and 6.01 × 10 11 Jones, respectively, demonstrating the ability to detect a weak light signal (Figure S5, Supporting Information). It is worth noting that the present GaSe nanobelt displays much better photoelectric performance than previously reported GaSe nanosheet, including mechanically exfoliated GaSe nanosheets [ 20,39 ] and gas‐phase grown GaSe nanosheets, [ 40 ] which is comparable to or even better than that of traditional UWBG DUV photodetectors [ 12–15 ] (shown in Table 1 ), making it a promising candidate for application in future high‐performance DUV photodetector‐based devices and systems.…”
Section: Resultsmentioning
confidence: 75%
“…Currently, commercially available DUV photodetectors (e.g., photomultiplier tubes and Si photodetectors) normally operate at high bias voltage or adopt elaborate filters to eliminate the effect of visible and near infrared spectra. [ 10,11 ] To overcome the drawbacks of high power consumption as well as costly and complicated fabrication, a variety of ultrawide‐bandgap (UWBG) semiconductors with bandgaps larger than 3.4 eV (the bandgap of GaN), such as Al x Ga 1–x N, [ 12 ] Zn x Mg 1–x O, [ 13 ] Ga 2 O 3 , [ 14 ] and diamond, [ 15 ] have been extensively explored. Various studies have shown that their relatively high radiation hardness and intrinsic visible blindness have indeed made them prominent candidates for highly sensitive DUV photodetection applications.…”
Section: Introductionmentioning
confidence: 99%
“…Light intensity was fixed at 1.2 mW. Responsivity ( R ) was calculated using the following equation [ 41–44 ] R = Ilight IdarkPλS where I light is the photocurrent, I dark is the dark current, P λ is the incident light power density (0.95 mW mm −2 ), and S is the illumination area. Figure 4c shows the spectral responsivity of four devices measured under UV–visible lights from 300 to 800 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from optical performance, we also investigated the mechanism of the carrier transport process of the IGZO/GaAs nanopillar heterostructure photodetectors. Figure a–d shows the light intensity dependent photocurrent of Schottky and heterostructure photodetectors by varying the light intensities from 7.9 to 78.7 mW cm −2 at −5 V. The measured photocurrent was fitted by the power law as following [ 41,51 ] Ilight = C Pλθ where C is a constant, θ is the empirical coefficient, I light is the photocurrent and P λ is the incident light power density. θ values can be extracted by using the linear fitting as indicated in Figure 6a–d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation